Guest

[cos a / ( cosec a + 1 )] + [cos a / ( cosec a – 1 )]= 2 tan a

[cos a / ( cosec a + 1 )] + [cos a / ( cosec a – 1 )]= 2 tan a
 

Grade:10

2 Answers

Satyam Kumar
39 Points
4 years ago
cos a/(coseca+1)+ cos a/(cosec a-1)=(cos a(cosec a-1)+cos a(cosec a+1))/(cosec^2a-1)=2cos a cosec a/cot^2a=2cos a tan^2a/sin a=2tan^2a/tan a=2tan aHence proved
Satyam Kumar
39 Points
4 years ago
cos a/(coseca+1)+ cos a/(cosec a-1)↪(cos a(cosec a-1)+cos a(cosec a+1))/(cosec^2a-1)↪2cos a cosec a/cot^2a↪2cos a tan^2a/sin a↪2tan^2a/tan a↪2tan aHence proved

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free